The Organization and Control of Teacherʼs Self-Educational Activities (on the Basis of V.O. Sukhomlynskyiʼs Pedagogical Heritage - Svitlana Gergul (Pedagogical Discourse, 2015)
On the basis of the archival, historical and pedagogical sources and little-known works the author of the article has carried out the holistic analysis of the problem of teacher’s self-education activity described in V. O. Sukhomlynskyi’s pedagogical heritage. The definition of self-education is given, the aim of teacher’s self-education activity is defined, its arrangement and checking for fulfillment are studied. The following stages of arrangement of teacher’s self-education activity are identified: preparatory (understanding and realizing of the necessity of self-education activity, deciding upon a theme of self-education, defining the purpose and matter of self-education, self-education work planning, deciding upon the research and educational sources which will be used by a teacher); practical (processing and deep study of the psychoeducational and methodical literature on the chosen problem of self-education, accumulation of pedagogical facts such as selection, study, research and analysis, implementation of new working methods into teacher’s practical activity, experiment); final (summing up of observations and acquired knowledge, drawing up of the results of teacher’s self-education activity).The following kinds of checking for fulfillment of teacher’s self-education activity are singled out and described: preliminary (it was carried out before the beginning of the school year in the form of individual conversation between a school head and a teacher about the main content of self-education and teacher’s individual self-education plan was to be checked); current (it was carried out in two directions: visiting lessons and out-of-school activities with pupils; periodic checking for the fulfillment of teacher’s individual self-education plan); final (it was carried out at the end of the school year).